Tradução e adaptação transcultural do domínio função física do Patient-Reported Outcomes Measurement Information System – PROMIS® - versão para a língua portuguesa - Braga, Diana de Abreu Costa (2015)
In 2004, the National Institutes of Health made available the Patient-Reported Outcomes Measurement Information System – PROMIS®, which is constituted of innovative item banks for health assessment. It is based on classical, reliable Patient-Reported Outcomes (PROs) and includes advanced statistical methods, such as Item Response Theory and Computerized Adaptive Test. One of PROMIS® Domain Frameworks is the Physical Function, whose item bank need to be translated and culturally adapted so it can be used in Portuguese speaking countries. This work aimed to translate and culturally adapt the PROMIS® Physical Function item bank into Portuguese. FACIT (Functional Assessment of Chronic Illness Therapy) translation methodology, which is constituted of eight stages for translation and cultural adaptation, was used. Fifty subjects above the age of 18 years participated in the pre-test (seventh stage). The questionnaire was answered by the participants (self-reported questionnaires) by using think aloud protocol, and cognitive and retrospective interviews. In FACIT methodology, adaptations can be done since the beginning of the translation and cultural adaption process, ensuring semantic, conceptual, cultural, and operational equivalences of the Physical Function Domain. During the pre-test, 24% of the subjects had difficulties understanding the items, 22% of the subjects suggested changes to improve understanding. The terms and concepts of the items were totally understood (100%) in 87% of the items. Only four items had less than 80% of understanding; for this reason, it was necessary to chance them so they could have correspondence with the original item and be understood by the subjects, after retesting. The process of translation and cultural adaptation of the PROMIS® Physical Function item bank into Portuguese was successful. This version of the assessment tool must have its psychometric properties validated before being made available for clinical use.